The Role of Color in Document of City Identity Case study: Lattakia city - علي أسعد; المعلم ريم; محمد رزان (Latakia University Journal -Engineering Sciences Series, 2020)
The city represents a reflection of the culture and civilization in society. Every city leaves its mark due to a combination of places, spaces, colors and smells, documents her identity and establish its permanent place in the memory of its inhabitants and visitors. Visual and aesthetic elements in cities are among the most important aspects that architectural and urban design aims to study, Since any defect in aesthetic aspects produces visual pollution in the public landscape, loss of identity and lead to negative effects (environmental, behavioral, economic, social, cultural ...) Hence, the problem of research is that Lattakia (As a case study) suffers from the absence of any visual optical system, where the colors are used randomly, unstudied and not linked to the function of the building, the nature of the region, its climate and its urban character, and the possibility of making any modification to the colors of existing buildings by people who do not have sufficient experience and Without being punished, Research Objective: is to shed light on the role of color and its importance and the extent of its effect in forming an integrated features picture of the city documents her identity. Where the color is of the most important visual and aesthetic characteristics, Lattakia city has been chosen as a case study as a tourist city that attracts many visitors from inside and outside the country. It must have a harmonious and beautiful architectural design. The research came as an attempt to find a solution by developing a research methodology that includes theoretical (a theoretical study of the concept of the city and the relationship between colors and architectural identity) analytical (analysis of some global and local models) and extrapolate (extrapolation of Visual color pollution in Lattakia) methods to reach conclusions and recommendations, the most important of which. To highlight the importance of color in documenting the identity of the city, find a scientific methodology for choosing the colors of building facades, in cities in general and in Lattakia in particular, Reflects its cultural and civilization heritage, with the possibility of adoption by the relevant authorities.